Factors influencing the utilization of Traditional Chinese Medicine in cancer treatment: a qualitative meta-synthesis of patient and healthcare professional perspectives - Xu, Runbing; Sun, Yanan; Liu, Yifei; Pan, Jiajun; Han, Yingying; Zhang, Xinyu; Zhao, Hequn; Li, Mengfei; Wu, Yu; Yu, Changhe; Jiang, Miao (Frontiers in Medicine, 2025)
BackgroundThe complementary role of Traditional Chinese Medicine (TCM) in cancer management has been widely acknowledged. However, its implementation continues to face numerous challenges. Identifying and elucidating the factors that influence the integration of TCM into cancer therapy is essential. Developing effective implementation strategies is crucial to transitioning from theoretical evidence to practical application.MethodsA total of nine databases were systematically searched from their inception until 1 October 2023. The review includes qualitative and mixed-method studies examining the attitudes and perceptions of patients and healthcare providers toward the use of TCM in cancer treatment. The studies included were evaluated using a quality assessment tool. An appropriate model or framework was to identify potential facilitators and impediments affecting TCM implementation. Based on the identified barriers, potential behavior change interventions were subsequently developed.ResultsA total of 39 studies are included in the review, comprising 31 qualitative and eight mixed-methods studies. The quality of these studies is acceptable. Key barriers to the implementation of TCM were identified as follows: insufficient knowledge and experience in TCM, neglect of details in doctor-patient communication, limited number of specialists, lack of funding, and absence of a multidisciplinary collaborative atmosphere. In response to these barriers, we recommend improving structured referral pathways, developing a structured communication manual, and other targeted interventions to enhance the integration of TCM in cancer care.ConclusionThis study identifies 48 factors that influence the implementation of TCM and tentatively proposes a series of intervention strategies. Future research should focus on localized empirical studies of factors and strategies in different healthcare settings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=421822, identifier CRD42023421822.